JISMONIY SHAXSLAR DAROMADLARINI DEKLARATSIYA ASOSIDA SOLIQQA TORTISH TIZIMINI TAKOMILLASHTIRISH MASALALARI (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
The composition of taxes collected from individuals and their equivalent payments, the procedure for calculating, submitting and paying each type of tax paid by individuals, the powers and duties of state tax authorities, the procedure for collecting taxes from individuals, practical The main content of the topic is the formation of appropriate knowledge, skills and competences in the study of problem solving issues, basic concepts and terms used in tax administration. "Taxation of natural persons" is a bilateral relationship between tax authorities and natural persons who pay taxes.